Design of Rain Water Harvesting Structure for Engineering Block - Vikas Garg (Polish Society of Ecological Engineering (PTIE), 2022)
Present work is a case study of rainwater harvesting needs and the measures being adopted for the northern region of Haryana, India, covering the districts of Rewari and Mahendergarh. The study was necessitated following the notification by Haryana Urban Development Authority to make rainwater harvesting mandatory for its urban estates. As per the notification: “each individual plot holder having a rooftop area of 100 sq. m. or more, is required to provide for suitable rainwater harvesting measures.” Keeping in view the available soil strata, average rainfall, rainfall intensity, social acceptability etc., a plan has been drafted to comprehensively utilize the rainfall water falling in the campus of Central University of Haryana, Mahendergarh, a campus of around 488 acres of area. Land area requirement for different suggested modes is likely to be a very small percentage of the total catchment’s area. In the first phase, ground water recharge structures for School of Engineering and Technology are suggested. Major objective of the study is to provide rainwater harvesting structures so that ground water storage is enhanced to an extent that it would suffice the drinking water needs of students and faculties residing in the campus. Another objective of the study is that these recharge structures will serve as models and infuse confidence in people to follow the good work initiated by the Haryana Urban Development Authority.